The concept of entropy. Relation between action and entropy - Badiali, J.-P. (Condensed Matter Physics, 2005)
The Boltzmann expression for entropy represents the traditional link between
thermodynamics and statistical mechanics. New theoretical developments
like the Unruh effect or the black hole theory suggest a new definition
of entropy. In this paper we consider the thermodynamics of black
holes as seriously founded and we try to see what we can learn from it in
the case of ordinary systems for which a pre-relativistic description is sufficient. We introduce a space-time model and a new definition of entropy
considering the thermal equilibrium from a dynamic point of view. Then we
show that for black hole and ordinary systems we have the same relation
relating a change of entropy to a change of action. Больцманівський вираз для ентропії представляє традиційний
зв’язок між термодинамікою та статистичною механікою. Нові
теоретичні результати типу ефекта Анру чи теорії чорних дір допускають нове означення ентропії. В цій статті ми розглядаємо
термодинаміку чорних дір як основу і пробуємо побачити, що можна
з неї отримати для випадку звичайних систем, для яких достатнім
є нерелятивістський опис. Ми вводимо модель простору-часу та
означення ентропії, розглядаючи термічну рівновагу з динамічної
точки зору. Далі ми показуємо, що для чорної діри та звичайних систем ми маємо однакове співвідношення, що пов’язує зміну ентропії
зі зміною дії.